Guillain-barré syndrome following brainstem infarction: a case report and pathophysiological hypothesis - Jiao, Shusheng; Li, Miaomiao; Zhi, Jianxia; Yu, Zengyang; Cheng, Xiaofang; Gong, Zihua (Frontiers in Immunology, 2025)
Guillain-Barré syndrome (GBS), the leading global cause of acquired neuromuscular paralysis, is classically defined as an immune-mediated polyradiculoneuropathy triggered by molecular mimicry between microbial antigens and peripheral nerve components. However, emerging clinical observations challenge the traditional paradigm by reporting GBS following noninfectious events. Notably, the plausible link between GBS and acute ischemic stroke remains unclear, despite isolated case reports suggesting a potential association. Here, we report a rare case of rapidly progressive GBS after acute left pontine infarction. A 72-year-old male with hypertension, type 2 diabetes, coronary heart disease, hyperhomocysteinemia, and a history of ischemic stroke presented with 13-hour acute right-leg weakness and dysarthria. No recent infections were reported. Brain MRI confirmed acute left pontine infarction (DWI hyperintensity/ADC hypointensity). Guideline-based stroke therapy (dual antiplatelet agents, high-intensity statin and comprehensive vascular risk factor management) led to near-complete recovery by Day 12. However, from hospital day 13 onward, he experienced acute neurological deterioration characterized by rapidly progressive flaccid quadriplegia (MRC grade 0/5 in all limbs) and generalized areflexia over five days. Cerebrospinal fluid (CSF) analysis revealed albuminocytological dissociation, and GBS (acute motor axonal neuropathy subtype) was confirmed through nerve conduction studies and electromyography. Serum and CSF anti-ganglioside antibody testing was negative. Intravenous immunoglobulin (IVIG; 0.4 g/kg/day for 5 days) combined with rehabilitation resulted in partial recovery (MRC 2/mRS 4 at 30-day follow-up; MRC 3/mRS 4 at 90-day follow-up). Our findings broaden the etiological spectrum of peripheral demyelinating diseases, and meanwhile highlight that GBS may be an under-recognized cause of post-stroke neurological deterioration, necessitating heightened clinical vigilance. Stroke-induced immunodepression may constitute a biologically plausible mechanistic link bridging cerebral ischemia and subsequent GBS development, and deeper investigation into its pathogenesis is warranted to elucidate its role in stroke-induced GBS variants.